Obstructive Jaundice Due to a Pancreatic Mass: A Rare Presentation of Acute Lymphoblastic Leukaemia in an Adult - Daniel, Sudin Varghese; Vani, Deven Harshad; Smith, Andrew Melvin; Hill, Quentin Antony; Menon, Krishna Viswanath (JOP. Journal of the Pancreas, 2016)
Context To highlight a rare presentation of acute lymphoblastic leukaemia. Case report A 39-year-old man presented with a 4 month history of weight loss and a 6 week history of upper abdominal pain radiating to the back with nausea and vomiting. Liver function tests showed an obstructive picture, full blood count was normal and on computerised tomography there was diffuse enlargement of the pancreas, with dilatation of the common bile duct and intra hepatic biliary radicles. Four weeks after presenting, the white cell count became elevated with blasts on the blood film and bone marrow biopsy revealed a precursor B cell acute lymphoblastic leukaemia. After induction chemotherapy his jaundice resolved, the pancreatic mass reduced in size and he is now in a complete remission. Conclusion Acute lymphoblastic leukaemia may mimic common causes of a pancreatic mass such as adenocarcinoma and should be considered as part of the differential diagnosis when atypical features are present. Image: Bone marrow trephine at presentation: cellular marrow with heavy infiltration by leukaemic blast cells.